THE KEY TO HEALTHY AGEING: Start Early, Stay Strong! - Leh Shii, Law (Faculty of Medicine and Health Sciences, 2025)
Healthy ageing requires a holistic approach across six dimensions: health, psychological well-being, Hfinances, housing , social engagement, and active leisure (Solhi et al., 2022). Nutrition is crucial for health preparation, and early dietary planning helps individuals navigate ageing smoothly. The Malaysian Dietary Guidelines for Older Persons (NCCFN, 2024) highlight six key messages for healthy ageing.